Relationship between Electrically Evoked Compound Action Potential Thresholds and Auditory, Language, and Speech Progress after Cochlear Implant Surgery - Motasaddi Zarandy, Masoud (Iran J Otorhinolaryngol, 2018)
INTRODUCTION: Electrically evoked compound action potential (ECAP) is an objective auditory response that can be used in the programing of cochlear implants. The aims of this study were to monitor ECAP thresholds and auditory, language and speech progress for 6 months after cochlear implant surgery and to evaluate any relationship between them. MATERIALS AND METHODS: Ten children with a mean age of 4.2 (±0.6) years and bilateral congenital and profound sensorineural hearing loss underwent cochlear implant surgery and post-operation auditory and speech training. The auditory, language, and speech abilities (Newsha level) and ECAP thresholds (for apical, medial and basal region of cochlea) were evaluated 1, 3 and 6 months after surgery. RESULTS: ECAP threshold showed no significant improvement in any of the evaluated areas in the 6 months after surgery (P>0.05); however, the Newsha level improved for all patients (P=0.00). CONCLUSION: There was no relationship between ECAP thresholds and auditory, language, and speech abilities (Newsha level) in the first 6 months after surgery. ECAP thresholds may be a poor indicator of improvement in auditory, language, and speech abilities, and depend on many factors.